Penetration into free abdominal cavity during transanal endoscopic rectal resection for adenoma - Yu. A. Gevorkyan; N. V. Soldatkina; V. E. Kolesnikov; D. A. Kharagezov; A. V. Dashkov; S. I. Poluektov; N. S. Samoylenko (Южно-Российский онкологический журнал, 2021)
Benign and malignant tumors are the most common diseases of the rectum and tend to grow. Various techniques have been developed for the treatment of rectal tumors: endoscopic electroexcision through a colonoscope, transanal removal of tumors, and transabdominal removal. The use of all these methods made it possible to determine their advantages and indications, as well as limitations and disadvantages. Technical advances in modern oncology resulted in developing a method for transanal tumor removal with a number of advantages: radical surgery, adequacy, and functionality. This technique can be used in benign and malignant rectal tumors. One of its main advantages involves a small number of postoperative complications, while intra- operative complications such as penetration into the free abdominal cavity during transanal endoscopic resection of the rectum are quite rare. It is also important that the method of transanal endoscopic resection of the rectum also has good oncological and functional results (according to various studies). We present a clinical case of penetration into the free abdominal cavity during transanal endoscopic rectal resection for adenoma. This case is also interesting in that the patient also had another complication – postoperative bleeding from the rectum, which required surgical intervention, also with the use of a minimally invasive approach.This clinical observation demonstrates successful suturing of penetrating openings into the abdominal cavity arising during transanal endoscopic removal of rectal tumors with the upper pole located above the pelvic peritoneum and effective minimally invasive tactics in the development of postoperative bleeding.